Bacterial Pathogens and Their Virulence Factors - Johnson, Douglas I. (Springer International Publishing, 2018)
Bacterial Pathogens and their Virulence Factors contains a detailed description of 32 major bacterial pathogens that affect human health and their associated virulence determinants. Chapter 1 gives an overview of the different types and classes of general virulence factors involved in host cell adherence and invasion, dissemination within the host, host cell damage, and evasion of host defense systems, as well as mechanisms by which these virulence factors are regulated. Chapters 2 through 33 give concise descriptions of the disease states associated with the 32 bacterial genera and their major pathogenic species, along with an in-depth description of the individual virulence factors that have been found to be functionally involved in pathogenicity. A detailed bibliography derived from primary literature and review articles accompanies each of these chapters, allowing the reader to delve more deeply into individual pathogens and their virulence determinants.Chapter 34 discusses the exciting possibilities and initial successes of using detailed information on a pathogen's virulence toolkit to design new therapeutics aimed at specific virulence traits.